Enchanted Europe: superstition, reason, and religion, 1250-1750 - Cameron, Euan (Oxford University Press, 2010)
'Enchanted Europe' offers a comprehensive account of Europe's long, complex relationship with its own folklore and popular religion. From debates over the efficacy of charms and spells, to belief in fairies and demons, Euan Cameron constructs a compelling narrative of the rise and fall of 'superstition' in the European mind.